Revisiting Omani legacy in Malaya through the Royal Kedah dress: reassessment - Mansor Majdin, Mohamad Firdaus; Ahmad H.Osman, Rahmah; Fathil, Fauziah; Yaapar, Md. Salleh; Al Zuheimi, Saleh (University of Management and Technology Lahore, Pakistan, 2022)
This paper seeks to examine the legacy of the Omani presence in the states of Malaysia, which arguably has made itself apparent in the royal dress of the Kedah Sultanate. This discovery indeed calls for further investigation, especially on how the Omani dress later became a model for Kedah royal dress which is famously known as Baju Muskat. Further analysis is essential to determine to what extent did the Kedah Sultanate adopted the Omani dress of the Muscati style and what aspects of the Kedah royal dress resemble the Omani dress substantially. Preliminary research indicates that there are few similarities that one can find between the Omani dress with that of the Kedah royal dress, which is said to be worn by the latter since the 17th century. Reading through the existing literature in the field also reveals one interesting picture that points to the underrepresentation of Omani individuals, merchants, and scholars in the Malay texts as the former tends to describe them, often as Arab traders, or Persian traders. In short, this paper has attempted to explore and examine the above-mentioned circumstances for a better understanding of the subject matter under study through a method of content analysis.